Calcium Oxalate Crystals in Leaves of the Extremophile Plant Colobanthus quitensis (Kunth) Bartl. (Caryophyllaceae) - Olman Gómez-Espinoza; Daniel González-Ramírez; Jairo Méndez-Gómez; Rossy Guillén-Watson; Alejandro Medaglia-Mata; León A. Bravo (Plants, 2021)
The presence of calcium oxalate (CaOx) crystals has been widely reported in the plant kingdom. These structures play a central role in various physiological functions, including calcium regulation, metal detoxification, and photosynthesis. However, precise knowledge about their possible roles and functions in plants is still limited. Therefore, the present work aims to study the ecotypic variability of Colobanthus quitensis, an extremophile species, concerning CaOx crystal accumulation. The CaOx crystals were studied in leaves of C. quitensis collected from different provenances within a latitudinal gradient (From Andes mountains in central Chile to Antarctica) and grown under common garden conditions. Polarized light microscopy, digital image analysis, and electron microscopy were used to characterize CaOx crystals. The presence of CaOx crystals was confirmed in the four provenances of C. quitensis, with significant differences in the accumulation among them. The Andean populations presented the highest accumulation of crystals and the Antarctic population the lowest. Electron microscopy showed that CaOx crystals in C. quitensis are classified as druses based on their morphology. The differences found could be linked to processes of ecotypic differentiation and plant adaptation to harsh environments.